(untitled) (Existential Analysis: Journal of the Society for Existential Analysis, 2016)
This paper introduces some key notions from the work of the early Greek Sceptics, namely Pyhrro of Ellis and Sextus Empiricus. It will consider whether they can offer a different perspective on the epoché and the possibility of performing a phenomenological enquiry. The paper begins by giving a brief overview of phenomenology as it is currently described. This is followed by a presentation of Pyhrro’s and Sextus’s philosophical stance and their understanding of the epoché, including their view as to how to approach phenomena. The following section examines how we can approach and see a phenomenon, what can prevent us from seeing what is in front of our eyes and how we can learn to look and see a phenomenon. The paper concludes by exploring if and in what way Husserl’s and Heidegger’s use of the epoché is in any way related to Pyrrho’s and Sextus’s description.